Pemahaman Mahasiswa Akuntansi Terhadap Implementasi Teknologi Akuntansi di Era Digital Universitas 17 Agustus 1945 Surabaya - Putri Rahayu; Hwihanus Hwihanus (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to understand accounting students' understanding of the implementation of accounting technology in the digital era at Universitas 17 Agustus 1945 Surabaya. Using a descriptive qualitative method, this study involved five students selected by purposive sampling, with data collected through an online questionnaire. The results showed that students' understanding of accounting technology varied. Three students felt that the technological skills they learned were sufficient to compete in the world of work, while the other two students felt the need to improve their understanding. All participants claimed to have used accounting software such as SPSS and SMART PLS during lectures, but the intensity and depth of use varied. The main challenges faced by students include the acceleration of technological developments, initial adaptation to complex software, and limited in-depth practical training. Some students feel overwhelmed in keeping up with the rapid development of technology, while others have difficulty in understanding accounting technology due to the lack of in-depth learning. This study concludes that although most students feel they have a fairly good understanding, increased access and practical training is needed to ensure they are ready to face technological challenges in the digital era.